Subjectivity and Śūnyatā: A Conceptual Bridge between Kierkegaard and Tsongkhapa - Yi, Jizhang (Buddhist Christian studies, 2026)
This paper explores the possibilities for a cross-cultural and inter-religious dialogue between Søren Kierkegaard and Tsongkhapa by examining whether Kierkegaard's concept of "truth is subjectivity" parallels Tsongkhapa's notion of "truth is śūnyatā (emptiness)." Although separated by time and cultural context, both thinkers challenge prevailing traditions and reimagine truth as a transformative, experiential process. Kierkegaard critiques intellectual elitism and classical foundationalism, emphasizing subjective engagement and personal commitment to existential truth. Tsongkhapa underscores the importance of philosophical reasoning and meditative practice in realizing the nonduality of conventional and ultimate truths. This paper argues that despite their distinct metaphysical assumptions, both view truth as dynamic and deeply connected to lived experience. In addition to a philosophical analysis of these parallels, the paper employs Conceptual Metaphor Theory to demonstrate how Kierkegaard's "truth is subjectivity" and Tsongkhapa's "truth is śūnyatā" reflect shared insights into the transformative and practical realization of truth.